Research Pertaining to the Agricultural Biodiversity in Relation to Conservation and Sustainable Development of Traditional Crops of Kusmi Block of Sidhi District of Madhya Pradesh, India - Mohammad Salim; Vivek Kumar Yadav (Recent Trends in the Study of Botanical Research Volume - 1, 2023)
Agricultural biodiversity serves as a reservoir facilitating the advancement of novel and progressive crop varieties. It is incontrovertible that agricultural biodiversity assumes a pivotal role in addressing not only our sustenance requirements but also our broader material necessities. Within the realm of agricultural biodiversity, an extensive genetic reservoir is conserved, furnishing a robust foundation for augmenting food outputs in the context of burgeoning populations within distinct microclimatic habitats. In tandem with enhancing production, the inherent variability inherently safeguards against pestilence and other maladies. The elemental requisites for human sustenance are readily procurable via the conduit of agricultural biodiversity. Moreover, the role of agricultural biodiversity extends to the equilibrium preservation of the ecosystem. Hence, in addition to its multifarious advantages, it mitigates geopolitical insularity. Ergo, the preservation of agricultural biodiversity emerges as an imperatively requisite pursuit for ensuring food availability, fostering sustainable progression, and safeguarding the reservoir of genetic diversity within the region. The present chapter is an attempt to discuss the agricultural biodiversity of Sidhi District, Madhya Pradesh, India.